Fintech services and the drivers of their implementation in small and medium enterprises - Moreira, Diana (2022)
Fintech has been one of the biggest agents of change in the financial sector worldwide, deserving an in-depth analysis as the aim of this study (including factors leading to its adoption, consequences, etc.). During the COVID-19 pandemic, the financial area and Fintech services allied to technology has increased efficiency, convenience, and security. To better understand this type of service, the research follows a quantitative methodology. The quantitative method included a questionnaire survey of companies that are Fintech customers, totaling 49 valid responses from firms (collected over a three-month period and which involved sending over a thousand emails to numerous companies). The response rate was low due to both the pandemic and the conjuncture with major war, which are generating uncertainty in business. The analysis was based on descriptive statistics, an assessment of the metric qualities of the scales, reliability and an Exploratory Factor Analysis, Pearson correlations and Hypothesis testing. The positive and significant effect of the technological context (perceived convenience, usefulness and effectiveness and perceived safety and trust) and the organizational context (ecological footprint reduction and internal cost reduction) on Fintech service adoption intention was confirmed. Hypothesis Three was partially confirmed since only consumer trends and reputation perception have a positive and significant effect on the intention to adopt Fintech by SMEs. The moderating effect of the environmental context in the relationship between the technological context and the intention to adopt Fintech by SMEs was partially proven, but the same was not verified in the relationship between the organizational context and the intention to adopt Fintech by SMEs. Portugal seems to be on the same adoption path as the rest of the western world, and Fintech services will undoubtedly increase, in a kind of revolution in which the strongest and those able to adapt to the markets and their needs will survive.